The effect of FOMC votes on financial markets - Madeira, C.; Madeira, J. (Review of Economics and Statistics, 2019)
This paper shows that since votes of members of the Federal Open Market Committee have been included in press statements, stock prices increase after the announcement when votes are unanimous but fall when dissent (which typically is due to preference for higher interest rates) occurs. This pattern started prior to the 2007–2008 financial crisis. The differences in stock market reaction between unanimity and dissent remain, even controlling for the stance of monetary policy and consecutive dissent. Statement semantics also do not seem to explain the documented effect. We find no differences between unanimity and dissent with respect to impact on market risk and Treasury securities.